E-Governance: A Global Perspective on a New Paradigm - Obi, Toshio (IOS Press, 2013)
ITU is the oldest international organization in the world. Going back 141 years to when, Napoleon Bonaparte and Queen Victoria signed a peace treaty in Germany At about the same time, people began to use the telegraph, which spread widely all around the world. To internationalize the telegraph, a standard was established, and in order to do so, international agreements were required